2006
DOI: 10.1136/sti.2005.016352
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial self medication for reproductive tract infections in two provinces in Lao People's Democratic Republic

Abstract: Objectives: To describe antimicrobial self medication for reproductive tract infections (RTI) including sexually transmitted infections (STI), and to explore the understanding and use of health information among the adult population self medicating with antimicrobials for RTI/STI in two provinces of Laos. This could contribute to quality improvement of RTI/STI management. Methods: Cross sectional community based study. Structured interviews (household survey) were conducted among 500 subjects aged 18 or more, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 15 publications
1
48
1
1
Order By: Relevance
“…Our results indicate that for this particular issue, the regulatory framework of the UAE is not effectively enforced. Antibiotic availability over-the-counter has been reported in many countries in Asia [9,[11][12][13][14][15], Africa [24,25], the Middle East [16,17,26,27], Latin America [18,28,29], Southern and Eastern Europe [19,[30][31][32][33], and America [20,21,34]. The high level of over-the-counter antibiotic sales is certainly not unique to the UAE.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our results indicate that for this particular issue, the regulatory framework of the UAE is not effectively enforced. Antibiotic availability over-the-counter has been reported in many countries in Asia [9,[11][12][13][14][15], Africa [24,25], the Middle East [16,17,26,27], Latin America [18,28,29], Southern and Eastern Europe [19,[30][31][32][33], and America [20,21,34]. The high level of over-the-counter antibiotic sales is certainly not unique to the UAE.…”
Section: Discussionmentioning
confidence: 96%
“…Of these, only 35.8% were prescribed by doctors, 13.8% were recommended by pharmacists and about half (50.4%) were sold on customers' request without prescription or advice from the pharmacist [16]. In two provinces of Lao People's Democratic Republic, 91% of respondents purchased non-prescription antibiotics from private pharmacies to treat reproductive tract infections and sexually transmitted diseases [15]. Some of the established reasons for the sale and use of antibiotics without prescription include privacy and a preference for remaining anonymous [37], high patient demand [38], and lack of public awareness and misconceptions about the efficacy of antibiotics [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conditions are worsened with inappropriate self medication of antibiotics. It has been reported that with lack of supervision from healthcare professionals, people in Jordan [6] and Laos [7] consumed non -prescribed antibiotics for treating common cold. This will lead to the increase of microbial resistance, an undesirable effect that causes antibiotic ineffectiveness and not only harmful to the patient but also to the society.…”
mentioning
confidence: 99%